2015
DOI: 10.1371/journal.pone.0120693
|View full text |Cite
|
Sign up to set email alerts
|

Sprouty2 in the Dorsal Hippocampus Regulates Neurogenesis and Stress Responsiveness in Rats

Abstract: Both the development and relief of stress-related psychiatric conditions such as major depression (MD) and post-traumatic stress disorder (PTSD) have been linked to neuroplastic changes in the brain. One such change involves the birth of new neurons (neurogenesis), which occurs throughout adulthood within discrete areas of the mammalian brain, including the dorsal hippocampus (HIP). Stress can trigger MD and PTSD in humans, and there is considerable evidence that it can decrease HIP neurogenesis in laboratory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…The normal morphology of neurons is the basis for maintaining their normal physiological function. Prolonged stress exposure can result in morphological damage to hippocampal neurons in mice, leading to a neuronal dysfunction ( Dow et al, 2015 ; Besnard and Sahay, 2016 ). The present study supports these findings and further revealed that the structural damage of neurons in the hippocampal CA1.…”
Section: Discussionmentioning
confidence: 99%
“…The normal morphology of neurons is the basis for maintaining their normal physiological function. Prolonged stress exposure can result in morphological damage to hippocampal neurons in mice, leading to a neuronal dysfunction ( Dow et al, 2015 ; Besnard and Sahay, 2016 ). The present study supports these findings and further revealed that the structural damage of neurons in the hippocampal CA1.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic variants at the GRK5 gene have been associated with the regulation in methadone dosage in heroin dependence ( 50 ). SPRY2 is an intracellular inhibitor of growth factors involved in stress sensitivity ( 51 ). TRIB2 is a member of the tribble family; risk alleles mapping to this gene have been also associated with methadone dose in an African Americans population ( 52 ).…”
Section: Discussionmentioning
confidence: 99%